A study about the disposal of solid waste of healthin a public hospital institution in Sant’ana do Livramento town - Araújo, Cristiane Ferreira de Souza; Machado, Mari Eldionara Rosa; Rodrigues, Paola Rosano; Fialho, Angela Andressa Rodrigues (Revista de Administração da UFSM, 2018)
This article was created with the purpose of improving studies in the field on the disposal of solid waste of health in a public hospital in the municipality of Sant’Ana do Livramento. To obtain the results, a qualitative orientation research was developed, conducting structured interviews with two persons responsible for the sectors that involve hospital waste. The answers of these interviews served as a theoretical basis for analysis and results, and the objectives of this study were achieved, mainly identifying the policy adopted by the hospital institution regarding solid health residues.